Nitrogen fixation by Pueraria lobata as a nitrogen source in the midstream sediment bar of a river - Asaeda, Takashi; Rashid, Md Harun; Ohta, Kohske (Ecohydrology, 2016)
It was assumed that the symbiotic N fixation in a floodplain site is highly affected by flood disturbances. To test this hypothesis, we collected soil and plant samples from several quadrats of the midstream flood plain of a relatively steep urbanized river that was subject to a different magnitude of flooding. Soil carbon and nitrogen contents had a significant positive correlation with the elevation of sites; i.e. they negatively correlated with a frequency of flood inundation. Soil pH values ranged between 6.0 and 7.23 at low elevation sites and 5.16 and 6.81 for high elevation sites. There was a significant difference (p < 0.001) in N fixation among sampling points, which suggests that flooding disturbs the process. A pH value of 6.5 is the best for N fixation; N fixation decreases while the pH increases or decreases. Site elevation also directly affected soil characteristics, especially nitrogen and carbon content. The fractionation of 15N value in leaf tissue (δ15N) suggests that N fixation is extensive when the total N (TN) is ≤ 0.3%. Below this TN, Pueraria lobata can derive up to 80% of their TN requirement from the atmosphere. Therefore, it can be concluded that site elevation, or flood pulses, affects the symbiotic N fixation in a floodplain by modifying the edaphic factors. Copyright © 2015 John Wiley & Sons, Ltd.